Students’ Perception of Using Kahoot as an Online Assessment - Muttaqin, Dedy Ahsan (LPPM Universitas Bumigora Mataram, 2024)
Kahoot is an innovative assessment tool for education. This article examined students’ views on using Kahoot as a tool for teaching English in an online setting. This study employs a quantitative-descriptive approach. The study focused on a population of eighth-grade students enrolled in an English course consisting of 37 participants. This investigation utilized a Likert Scale and conducted interviews to gather data. The statements were categorized into five distinct forms: Strongly Agree (SA), Agree (A), Neutral (N), Disagree (D), and Strongly Disagree (SD). As indicated by their score of 1073, the majority of students were statistically neutral. Students perceive Kahoot as an enjoyable and user-friendly application with features that foster a constructive learning environment and promote healthy competition. This study’s findings indicate a positive development among students at SMPN 1 Lingsar utilizing Kahoot, highlighting engagement, motivation, competitiveness, and concentration. In summary, Kahoot offers an intuitive interface and appealing design that encourages student engagement in learning.